A monoclonal antibody against human thrombospondin inhibits platelet aggregation. - Dixit, V M (1985)
A monoclonal antibody (C6.7) has been generated against the calcium-replete form of human platelet thrombospondin (TSP). C6.7 is specific for TSP as determined by both competitive radioimmunoassay and immunoprecipitation. This antibody inhibits both thrombin- and A23187-induced aggregation of gel-filtered platelets in a concentration-dependent manner without affecting the secretion of serotonin. The epitope on TSP recognized by C6.7 has been localized to an 18-kDa fragment that is present in mild chymotryptic digests of TSP. This fragment is disulfide-linked to a 120- to 140-kDa fragment in unreduced digests, and both reduction and denaturation are required to separate the 18-kDa peptide from the larger fragments. A 25-kDa heparin binding domain is also present in the chymotryptic digest. However, the 18-kDa peptide is distinct from the heparin binding domain. The amino acid sequence at the NH2 terminus of the 18-kDa fragment is Asp-Thr-Asn-Pro-Thr-Arg-Ala-Gln-Gly-Tyr-.